0D to 3D ZnO nanostructures and their luminescence, magnetic and sensing properties: Influence of pH and annealing. (January 2017) - Shingange, K.; Tshabalala, Z.P.; Dhonge, B.P.; Ntwaeaborwa, O.M.; Motaung, D.E.; Mhlongo, G.H.
Graphical abstract: Abstract: Herein, we report on a successful synthesis of ZnO nanostructures with different particle morphologies using the microwave-assisted hydrothermal method. The effect of varying the pH before and after annealing at 450 °C on the particle morphology was evaluated. According to scanning electron microscopy (SEM), electron paramagnetic resonance (EPR), photoluminescence (PL) and Brunauer Emmett Teller (BET) surface area investigations, variation of pH during preparation phase have a significant effect on the morphology, defect structure and surface area of the ZnO nanostructures. Gas sensing performances of the ZnO nanostructures were investigated for methane (CH4 ), carbon monoxide (CO), ammonia (NH3 ) and hydrogen (H2 ) gases at an optimized operating temperature of 250 °C. ZnO sensors displayed comparable responses to these gases owing to variation in their morphology, surface area and porosity as well as defects induced by an increase in pH. The as prepared ZnO based sensors showed the higher response or selectivity to CO gas while the annealed ZnO based sensors showed the higher response or selectivity to NH3 gas.